La poliglòssia en la predicació de Vicent Ferrer. - FRANCÉS, ANTONI FERRANDO (Scripta, 2020)
Many of Vicent Ferrer's sermons have come down to us thanks to copies of the reportationes made by the stenographers who accompanied him on his missionary travels through various countries in Western Europe (1399-1419). They are not, therefore, faithful reproductions of Ferrerian orality, but they do reflect its basic features. The textual examination of these features and the critical analysis of the statements made by the witnesses of the process of canonization of Vicent Ferrer (1453- 1454) show that the Valencian Dominican, who in his preaching always tried to approach his listeners linguistically, adopted the Romance languages of the countries he visited, as we know that, in addition to Latin and to his mother tongue --Catalan or Valencian--, he was fluent in Aragonese, Castilian, French, Occitan and Italian.